Principles for teaching practicum and their particularization by associate teachers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Brownie, Dennis Edward (Massey University, 1990)
An apparent lack of substantiated guide-lines for carrying out school based teacher education sessions was perceived by this author. This concern motivated the present investigation of those practical aspects of teacher education frequently known as practicum. Following a review of relevant literature, commonly held principles were derived. It is argued that these principles, if followed by student-teachers, teacher educators and associate teachers, should result in effective practicum. Forty professional educators recorded how they put the seven principles for practicum into practice. These teaching practices were analysed and grouped into generic categories each with supporting criteria. Results provided potentially useful reference material for those involved in teaching practicum. Validity for the principles was established in terms of Ashcroft's learning determinants and Burke's model of teacher development. Results of this analysis indicated that the listed behaviours had potential to maximize student-teacher learning. The study concluded that the seven principles, behaviour categories and criteria provide student-teachers, teacher educators and associate teachers with a valid tool for directing practical aspects of teacher education.
Keywords: Teachers Training